Values associated with Nordic Walking: An international cross-sectional survey among individuals practicing walking with poles. - Wioletta Szymczak; Krzysztof Jurek; Monika Dobrogowska (PLoS ONE)
Introduction The article is devoted to the sociological exploration of the social phenomenon that Nordic Walking has become in Europe and worldwide over the recent decades. Aim It is based on the results of original international sociological research study on the issue of sociodemographic profiles of Nordic Walkers in the context of the values associated with this sports activity. Methods A cross-sectional quantitative study with convenience sampling study was performed among 416 Poles, 132 Europeans from 11 countries (Germany, the UK, Spain, France, Italy, Portugal, Ireland, Denmark, Austria, Sweden, and Norway), and 212 participants from 5 non-European countries (the USA, Canada, Australia, New Zealand, and Japan). The study used an author's tool that included questions concerning the ways of doing Nordic Walking and its and social and organizational contexts, its classification and interpretation as a health-related, recreational, or sports activity, its position in the space of everyday life and in the sphere of preferred values, motives for walking with poles, meanings attributed to this activity, and the individual and social benefits associated with it. Results The values most often associated with practicing Nordic Walking belong to the personal and psychophysical spheres. Their dominant position suggests that this activity is a complex one and that its advantages are not restricted to its motor aspects or to contact with nature. It is not a simple activity of walking with poles, as the initial stereotypes seem to suggest, but a kind of movement with a defined framework and a set of principles, engaging the physical and personal spheres of those who practice it, having a cultural meaning, and marked by cultural rootedness. Conclusion The research results can be useful for health care experts and for those responsible for building prevention strategies in various social groups. This is because they draw attention to the category of accessible and at the same time effective activities, with high individual and social potential. At the same time, they show that an important element of promotion strategies and social campaigns aimed at popularizing sport and healthy lifestyle should be axiological categories as significant predictors of individuals' actions and decisions.